Nano Clay Effect on Morphology, Mechanical Properties and Water Absorption of Vinyl Ester-Based Nanocomposites - Effat Jowdar; mohammad hossein Beheshty; mohammad atai (علوم و تکنولوژی پلیمر, 2012)
Nanocomposites based on vinyl ester resin (Derakane 470-300) and nano clay (Cloisite 30B) were prepared. The effect of clay content of 1, 3 and 5% (by weight) on the morphology, mechanical properties and water absorption of vinyl ester resin nanocomposites were studied. The nanocomposites were characterized  using  small-angle X-ray  scattering  (SAXS),  feld  emission  scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) and mechanical property measurements. SAXS and TEM images revealed a fully exfoliated morphology for clay content of 1 and 3% and an intercalated morphology for clay content 5%. Mechanical tests results showed that the vinyl ester nanocomposites have signifcantly better mechanical properties than neat vinyl ester resin. It is also found that water absorption drops in all specimens containing nano caly, and it is reduced to half its value with respect to the neat resin when the Cloisite 30B content is only 1%. The hardness of vinyl ester samples increased from 40 to 57 Barcol (approximately 43% increase) with by incorporating nanoclay of 1%.